Clomazone Leaching Estimate in Soil Columns Using the Biological Method - PEREIRA,G.A.M. (2017)
ABSTRACT The chemical control of weed is a necessary practice in large-scale agriculture. However, when herbicides are used in the wrong way, they can remain into soil for long periods and/or be leached in its profile, and they may even contaminate groundwater. In this research, clomazone leaching in soil samples collected from different Brazilian regions was estimated by biological method. To do so, columns containing soils were used, and samples were collected every 5 cm. After preparing columns and applying a 1,500 g a.i. ha-1 clomazone dose, rain simulation was performed. Sorghum was used in order to detect the herbicide. More than 60% similarity was found for the studied variables; it was chosen to use only data referring to toxicity percentage. Clomazone did not cause reduction in sorghum cultivated in Organosol, thus indicating a strong herbicide sorption in this soil. Increased pH in Oxisol reduced leaching. More rainfall caused increased herbicide leaching in Oxisol (pH 5.1) and Quartzarenic Neosol. The highest leaching occurred in soils with lower pH and lower organic matter content. It is possible to conclude that, in soils with higher organic matter content, clomazone has lower risks of being leached.